SOUTHERN SCUM GO HOME! A SLOVENE CULT NOVEL IN THE LIGHT OF BALKANISM - Reiman, Judit (Porównania, 2014)
„Czefurzy raus!” by Goran Vojnović is a Slovene cult novel narrated by a Bosnian teenager living in a Ljubljana housing estate, an immigrant ghetto. The boy, while relating about his adventures and experiences in a mixed Bosnian-Slovene language which is the most conspicuous evidence of his uprootedness and alienation, in an ironic and sometimes funny way recalls the situation in post-Yugoslav spaces with their constant cultural conflict between Central Europe and the Balkans with the eyes of the stigmatized and humiliated hero who is deprived of a chance for a better life. The paper shows how the topoi of nesting orientalism and nesting balkanism referring to Bosnians and Slovenes are thematized in the novel and represents an attempt to describe why the expected cultural transfer could not succeed. The starting point of our analysis is the theory of Maria Todorova, who introduced the concept of nesting balkanisms on the basis of nesting orientalisms.